Encyclopaedia of mathematical physics Vol.I : mathematical physics - Singh Mapal (Anmol publications, New Delhi, 2006)
Physics
ENGLISH
Keywords: Encyclopaedia of mathematical physics Vol.I : mathematical physics; Physics; Physics